Sankcijų poveikis komerciniam arbitražui - Zenevičius, Nortautas; Zokaitė, Justina (Vilnius University Open Series, 2024)
Impact of sanctions on commercial arbitration. Justina Zokaitė. Nortautas Zenevičius. This research paper analyses the possible effects of sanctions on commercial arbitration. The study analyses whether the impact of sanctions has an impact on the initiation of an arbitration dispute, arbitrability, applicable law and the enforcement of an arbitral award (the latter in relation to public policy). The article assumes that sanctions do not affect the initiation and, normally, the arbitrability of a dispute. However, sanctions may have an impact on the applicable law - an arbitrator dealing with a dispute between parties is unlikely to be able to ignore the applicable sanctions, which constitute mandatory rules. Similarly, disregard of sanctions may lead to a breach of international public policy. In the latter case, however, only sanctions imposed by the United Nations Security Council are recognised as part of international public policy. In contrast, sanctions imposed by individual States or even by the European Union will not necessarily be in conformity with international public policy.